2002
DOI: 10.1172/jci0215564
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ protects short-term ovarian carcinoma cell lines from CTL lysis via a CD94/NKG2A-dependent mechanism

Abstract: IFN-gamma regulates the immunogenicity of target cells by increasing their expression of HLA class I molecules. This facilitates the T cell receptor-mediated recognition by CD8(+) T cells but decreases target cell sensitivity to lysis by NK cells due to engagement of inhibitory NK receptors. In this study, short-term tumor cell lines from patients with advanced ovarian carcinomas were established. We demonstrate the paradoxical finding that IFN-gamma treatment of these short-term ovarian carcinoma cell lines (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 151 publications
(94 citation statements)
references
References 50 publications
7
86
0
1
Order By: Relevance
“…This data is in agreement with previous reports showing a downregulation of HLA-G1 cell-surface expression upon in vitro culture of renal carcinoma cell lines 16 and short-term ovarian carcinoma cell lines. 18 Interestingly, we found that loss of HLA-G1 mRNA in melanoma cells is associated with a selective switch in HLA-G alternative splicing toward HLA-G2 expression. This process is of particular interest since it abrogates the role of HLA-G1 in tumor escape from NK lysis.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This data is in agreement with previous reports showing a downregulation of HLA-G1 cell-surface expression upon in vitro culture of renal carcinoma cell lines 16 and short-term ovarian carcinoma cell lines. 18 Interestingly, we found that loss of HLA-G1 mRNA in melanoma cells is associated with a selective switch in HLA-G alternative splicing toward HLA-G2 expression. This process is of particular interest since it abrogates the role of HLA-G1 in tumor escape from NK lysis.…”
Section: Discussionmentioning
confidence: 75%
“…cDNA were prepared from 1-5 lg of total RNA using Ready To Go TM kit and oligo (dT) [12][13][14][15][16][17][18] , according to the manufacturer's recommendations. For HLA-G1 to -G5 transcript detection, PCR amplification and hybridization of the PCR products were performed as previously described.…”
Section: Isolation Of Rna Reverse Transcription Pcr Amplification Amentioning
confidence: 99%
See 1 more Smart Citation
“…Blood from healthy donors was obtained from the Blood Centre at the Karolinska University Hospital. Lymphocytes were enriched by density gradient centrifugation (Ficoll-Hypaque; Amersham Biosciences) as previously described (26). Cells were frozen in 10% DMSO (Sigma-Aldrich) and 90% heat-inactivated FBS (Invitrogen) and stored in liquid nitrogen.…”
Section: Cellsmentioning
confidence: 99%
“…Furthermore, expression of activating killer cell Ig-like receptors (KIR) on CD4 1 T cells has been associated with severe disease manifestations in RA patients [17]. Inhibitory receptors, however, seem to shut of the activation program in a more dominant fashion leading to abrogation of TCR signaling cascades [18,19]. The expression of inhibitory receptors has also been suggested to protect differentiated cells from activation-induced cell death, thereby taking part in the formation and survival of memory T cells [20].…”
Section: Introductionmentioning
confidence: 99%